Teacher self-perceptions of effectiveness: a study in a district of Kenya - Onderi, Henry; Croll, Paul (Routledge, 2009)
Background and purpose: The paper reports a study of the perceptions of teachers in secondary schools in the Gucha district of Kenya of their own effectiveness, the structure of their self-perceptions, variations in self-perceived effectiveness and the relationship between self-perceptions of effectiveness and the examination performance of their students. Design and methods: Data were based on questionnaires completed by 109English and mathematics teachers from a random sample of 30 schools in the Gucha district of Kenya. Pupil examination results were also collected from the schools. Results: Three dimensions of self-perceived effectiveness emerged from a factor analysis. These were: pedagogic process, personal and affective aspects of teaching and effectiveness with regard to pupil performance. Teachers tended to rate themselves relatively highly with regard to the first two, process-oriented, dimensions but less highly on the third, outcome-oriented, dimension. Self-ratings for pupil outcomes correlated with pupil examination performance at school level. Conclusions: The results show that these teachers can have a sense of themselves as competent classroom performers and educational professionals without necessarily having a strong sense of efficacy with regard to pupil outcomes.
Keywords: teacher self-perceptions; teacher self-efficacy; secondary education; Kenya